Kriminalitas dalam Novel Bandung Menjelang Pagi Karya Brian Khrisna - Karuniawan, Dwiky Yoga; Anas Ahmadi (ALFABETA: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2025)
The aim of this research is to describe the forms of criminality depicted in the novel Bandung Menjelang Pagi by Brian Khrisna and to explore the underlying factors that contribute to the emergence of such criminal acts within the narrative. This research employs a qualitative approach with a descriptive-analytical research design. The data in this study consist of sentences in the novel that represent criminal actions and their causes. The primary data source is the novel Bandung Menjelang Pagi by Brian Khrisna, supported by secondary data in the form of books on literary sociology and relevant scholarly articles on the study of criminality. Data collection was carried out using observation and note-taking techniques by repeatedly reading the text to identify and mark relevant passages. The data were analyzed using content analysis combined with a literary sociology approach. The results of the study reveal three types of criminality portrayed in the novel: theft, physical violence, and drug trafficking. Furthermore, the study identifies economic conditions, social structural conditions, and environmental conditions as contributing factors to the criminal acts. Keywords: crime, society, novel, literary sociology